A way to explore the existence of "immortals" in cancer registry data – An illustration using data from ICBP SURVMARK-2. (February 2022) - Andersson, Therese M.-L.; Rutherford, Mark J.; Myklebust, Tor Åge; Møller, Bjørn; Arnold, Melina; Soerjomataram, Isabelle; Bray, Freddie; Elkader, Hazem Abd; Engholm, Gerda; Huws, Dyfed; Little, Alana; Shack, Lorraine; et al.
Abstract: Background: Accurately recorded vital status of individuals is essential when estimating cancer patient survival. When deaths are ascertained by linkage with vital statistics registers, some may be missed, and such individuals will wrongly appear to be long-term survivors, and survival will be overestimated. Interval-specific relative survival that levels off above one indicates that the survival among the cancer patients is better than expected, which could be due to the presence of immortals. Methods: We included colon cancer cases diagnosed in 1995–1999 within the 19 jurisdictions in seven countries participating in ICBP SURVMARK-2, with follow-up information available until end-2015. Interval-specific relative survival was estimated for each year following diagnosis, by country and age group at diagnosis. Results: The interval-specific relative survival levels off at 1 for all countries and age groups, with two exceptions: for the age group diagnosed at age 75 years and above in Ireland, and, to a lesser extent, in New Zealand. Conclusion: Overall, a subset of immortals are not apparent in the early years within the ICBP SURVMARK-2 study, except for possibly in Ireland. We suggest this approach as one strategy of exploring the existence of immortals, and to be part of routine checks of cancer registry data. Highlights: If all deaths are not ascertained in cancer registries survival gets overestimated. Interval-specific relative survival that levels off above one could indicate this problem. This was investigated within the ICBP SURVMARK-2 study. Overall, a subset of immortals is not apparent, except for possibly in Ireland. We suggest this approach be part of routine checks of cancer registry data.